2013
DOI: 10.1080/13216597.2012.737816
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Chinese state media: The influence of education, Internet, and government

Abstract: The current study conducted a series of data analyses of the China General Social Survey (CGSS) 2008, the latest national survey of urban and rural households investigating the social structure and quality of life in China. Based on a recently conducted national survey, the study focuses on trust that Chinese citizens place in their state media, and explores the extent to which the trust is influenced by viewers' education, online news exposure, and trust in government. Overall, this study demonstrates a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…1 It has also been suggested that the censored media in mainland China may actually encourage more Chinese people to discuss forbidden and hidden news, as well as political events, online (Roberts, 2015). A study conducted by Xu (2013) demonstrates that trust in online news is related to the feeling that the Internet offers information which the mainstream channels do not.…”
mentioning
confidence: 99%
“…1 It has also been suggested that the censored media in mainland China may actually encourage more Chinese people to discuss forbidden and hidden news, as well as political events, online (Roberts, 2015). A study conducted by Xu (2013) demonstrates that trust in online news is related to the feeling that the Internet offers information which the mainstream channels do not.…”
mentioning
confidence: 99%
“…First, national advertising can reach a large number of audiences, which suggests low specificity and high generality, and thus, it is suitable for the purpose of brand-building (Sridhar et al 2016). The brand-building functionality of national advertising is further strengthened because national media channels such as China Central Television (CCTV) are generally regarded as trustworthy information sources in China (Xu 2013). By contrast, local advertising is highly relevant to specific local markets, and thus, the goal of local advertising is more related to generating immediate sales and it is usually more short-term focused (Popkowski Leszczyc and Rao 1990).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an entertainment program with no political pretentions, IYAO enjoys a certain degree of editorial, personal, and financial independence even under China’s strict regime of ideological control. This relative operational autonomy, or “semi-independent” space (Huang, 2000), tends to destabilize media practices in a system where the media are still subject to state control (Xu, 2013). As I shall show in the following sections, the transformation that IYAO underwent under government regulation exemplifies the power interplay between media commercialization and political censorship in the Chinese media industry.…”
Section: Reflexive Construction Of Desiring Subjects In Chinese Mediamentioning
confidence: 99%